A note on the spike in recorded mortality of humpback whales (Megaptera novaeangliae) in Western Australia - Coughran, Douglas K.; Gales, Nick J.; Smith, Holly C. (J. Cetacean Res. Manage., 2023)
An unprecedented number of humpback whales (n = 46) from Breeding Stock D (BSD) were found dead or dying on Western Australian beaches in 2009. This compares to an average of less than four stranded humpback whales in each year in the period between 1989 and 2008. The recorded number of humpback whales on beaches in the year preceding this peak (2008, n = 13) and the two years following the peak (2010, n = 16; 2011, n = 17) were also above the long term average. In 2012 (n = 7), the numbers of stranded whales was closer to the longer term average. The majority of stranded individuals were either calves (44%) or juveniles/sub-adults (49%), with only 7% classified as adults. Most whales appeared emaciated. There were insufficient data to determine cause of death. Three possible hypotheses to explain this spike in mortality are proposed: (1) the increase in mortality of BSD was an artefact of increased detection and reporting; (2) the increase was temporary and transitory; and (3) the spike in mortality represents the start of an increasing trend in mortality as the population approaches carrying capacity. We suggest that hypothesis two is the most plausible but on-going monitoring will be required to test this.